ON THE SIMILARITIES AND DIFFERENCES BETWEEN THE METHODS OF ANTITHESIS AND OXYMORON (Scientific journal of the Fergana State University, 2023)
The article discusses the antithesis of lexical-semantic and lingvostylistic figures which serve to increase the effectiveness of speech, as well as unifying and distinguishing features of oxymoron.